Anaplasma marginale: Molecular discrimination, recombinant expression and characterization of major surface protein 2 - Junsiri W. (2023)
A. marginale's major surface protein 2 (MSP2) is an immunodominant protein that is encoded by a multigene family. Phylogenetic analysis revealed that the msp2 sequence Thailand strain was clustered in third clade, with similarity values between 90.4 and 100%. The haplotype diversity showed 10 haplotypes of the msp2 genes. The entropy analysis of the nucleic and amino sequences revealed 289 and 117 high entropy peaks, respectively. Interestingly, one predicted allele belonging to MHC-II represented the hypervariable region (HVR) of MSP2. A. marginale's recombinant MSP2 (rAmMSP2), which has a molecular weight of 42 kDa, was examined in SDS-PAGE. Antigenicity of rAmMSP2 (42 kDa) and AmMSP2 (36 kDa) showed the conserved epitopes. The distribution of AmMSP2 on infected erythrocytes' membrane and outside was demonstrated by immunofluorescence detection. Therefore, the rMSP2 could be utilized in the establishment of immunodiagnostic tools and vaccine approaches for the monitoring of anaplasmosis.